Geo-ecological Environment of Thar desert: A case study of Bikaner District: Mineral resources and ecological characteristics of Bikaner District in Thar desert (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Rajasthan enjoys a very significant place in mineral deposits and their production. PresentlyRajasthan produces 42 varieties of major and 23 minor minerals. The state is soul producer of Jasper,Garnet of Gem variety and wollastonite in India. Almost the entire production of Zinc concentrate, gypsum,fluorite (graded), asbestos and calcite is reported to be found from Rajasthan. Besides Rajasthan is theleading producer of lead concentrate (77), soap stone (85), ochre(66) and felspar (70) in thecountry.